2011
DOI: 10.1029/2010ja016424
|View full text |Cite
|
Sign up to set email alerts
|

Development of parallel electric fields at the plasma sheet boundary layer

Abstract: [1] Many measurements of auroral particles, in particular recent measurements from the FAST satellite, indicate that the auroral electron distribution is often broad in energy and field-aligned in pitch angle. Such electrons are seen in conjunction with strong kinetic Alfvén waves with small perpendicular wavelength, and so the aurora produced by these electrons has been termed the "Alfvénic aurora." The Alfvénic aurora is predominant at the polar cap boundary of the aurora as well as in the auroral arc that b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 103 publications
1
35
0
Order By: Relevance
“…The parallel displacement current is ignored in the runs shown. However, in principle it should be present and can be included for cases where parallel electric fields are expected to develop [ Song and Lysak , , ; Lysak and Song , , ]. Ohmic currents in the ionosphere are included on the right‐hand side of Ampere's law.…”
Section: Model Descriptionmentioning
confidence: 99%
“…The parallel displacement current is ignored in the runs shown. However, in principle it should be present and can be included for cases where parallel electric fields are expected to develop [ Song and Lysak , , ; Lysak and Song , , ]. Ohmic currents in the ionosphere are included on the right‐hand side of Ampere's law.…”
Section: Model Descriptionmentioning
confidence: 99%
“…Finally, instabilities generating KAWs in plasma with transverse density modulations have been considered by Wu and Chen []. Similar ideas involving dissipative mechanisms related to interaction of Alfvén waves or KAWs and phase mixing have been examined in the context of the magnetospheric plasma sheet [ Lysak and Song , ] and in coronal loops [ Ofman and Aschwanden , ]. It has been shown that ion‐scale shear Alfvén waves can be excited by ion beams in the solar wind [ Hellinger and Trávníček , , ], and these can contribute to the formation of KAWs [ Nariyuki et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the broadening effect due to the perpendicular group velocity of the kinetic Alfven wave, phase mixing, which is due to the inhomogeneity of plasma perpendicular to the ambient magnetic field [ Lysak and Song , , ], and nonlinear effects, particularly the convective nonlinearity in the perpendicular equation of motion [e.g., Seyler , , ; Chaston and Seki , ], can narrow the scale of these Alfven waves. These effects need to be carefully investigated in future researches that expand our 1‐D kinetic model to a multidimensional one.…”
Section: Discussionmentioning
confidence: 99%